Pharmacological Therapy in the Heart as an Alternative to Cellular Therapy: A Place for the Brain Natriuretic Peptide? - Nathalie Rosenblatt-Velin; Suzanne Badoux; Lucas Liaudet (Stem Cells International)
The discovery that stem cells isolated from different organs have the ability to differentiate into mature beating cardiomyocytes has fostered considerable interest in developing cellular regenerative therapies to treat cardiac diseases associated with the loss of viable myocardium. Clinical studies evaluating the potential of stem cells (from heart, blood, bone marrow, skeletal muscle, and fat) to regenerate the myocardium and improve its functional status indicated that although the method appeared generally safe, its overall efficacy has remained modest. Several issues raised by these studies were notably related to the nature and number of injected cells, as well as the route and timing of their administration, to cite only a few. Besides the direct administration of cardiac precursor cells, a distinct approach to cardiac regeneration could be based upon the stimulation of the heart’s natural ability to regenerate, using pharmacological approaches. Indeed, differentiation and/or proliferation of cardiac precursor cells is controlled by various endogenous mediators, such as growth factors and cytokines, which could thus be used as pharmacological agents to promote regeneration. To illustrate such approach, we present recent results showing that the exogenous administration of the natriuretic peptide BNP triggers “endogenous” cardiac regeneration, following experimental myocardial infarction.